Primary Motor Cortex Excitability Is Modulated During the Mental Simulation of Hand Movement. (16th February 2017) - Hyde, Christian; Fuelscher, Ian; Lum, Jarrad A.G.; Williams, Jacqueline; He, Jason; Enticott, Peter G.
Abstract: Objectives: It is unclear whether the primary motor cortex (PMC) is involved in the mental simulation of movement [i.e., motor imagery (MI)]. The present study aimed to clarify PMC involvement using a highly novel adaptation of the hand laterality task (HLT).Methods: Participants were administered single-pulse transcranial magnetic stimulation (TMS) to the hand area of the left PMC (hPMC) at either 50 ms, 400 ms, or 650 ms post stimulus presentation. Motor-evoked potentials (MEPs) were recorded from the right first dorsal interosseous via electromyography. To avoid the confound of gross motor response, participant response (indicating left or right hand) was recorded via eye tracking. Participants were 22 healthy adults (18 to 36 years), 16 whose behavioral profile on the HLT was consistent with the use of a MI strategy (MI users).Results: hPMC excitability increased significantly during HLT performance for MI users, evidenced by significantly larger right hand MEPs following single-pulse TMS 50 ms, 400 ms, and 650 ms post stimulus presentation relative to baseline. Subsequent analysis showed that hPMC excitability was greater for more complex simulated hand movements, where hand MEPs at 50 ms were larger for biomechanically awkward movements (i.e., hands requiring lateral rotation) compared to simpler movements (i.e., hands requiring medial rotation).Conclusions: These findings provide support for the modulation of PMC excitability during the HLT attributable to MI, and may indicate a role for the PMC during MI. ( JINS, 2017, 23, 185–193)